Association Analysis of Markers Derived from Starch Biosynthesis Related Genes with Starch Physicochemical Properties in the USDA Rice Mini-Core Collection - Li, Kehu; Bao, Jinsong; Corke, Harold; Sun, Mei (Frontiers in Plant Science, 2017)
Rice eating and cooking quality is largely determined by starch physicochemical properties. The diverse accessions in the USDA rice mini-core collection (URMC) facilitate extensive association analysis of starch physicochemical properties with molecular markers specific to starch biosynthesis related genes. To identify significant trait-marker associations that can be utilized in rice breeding programs for improved starch quality, we conducted two association analyses between 26 molecular markers derived from starch biosynthesis related genes and 18 parameters measured of starch physicochemical properties in two sets of the mini-core accessions successfully grown in two environments in China. Many significant trait-marker associations (P < 0.001) were detected in both association analyses. Five markers of Waxy gene, including the (CT)n repeats, the G/T SNP of intron 1, the 23 bp sequence duplication (InDel) of exon 2, the A/C SNP of exon 6, and the C/T SNP of exon 10, were found to be primarily associated with starch traits related to apparent amylose content (AAC), and two markers targeting the 4329-4330 bp GC/TT SNPs and 4198 bp G/A SNP of SSIIa gene were mainly associated with traits related to gelatinization temperature (GT). Two new haplotypes were found in the mini-core collection based on the combinations of the 23 bp InDel and three SNPs (G/T of intron 1, A/C of exon 6, and C/T of exon 10) of Waxy gene. Furthermore, our analyses indicated that the (CT)n polymorphisms of Waxy gene had a non-negligible effect on AAC related traits, as evidenced by significant variation in AAC related traits among rice accessions with the same Waxy SNPs but different (CT)n repeats. As the five Waxy markers and the two SSIIa markers showed consistent major effects on starch quality traits across studies, these markers should have priority for utilization in marker-assisted breeding.